Focal hand dystonia due to hemorrhage of the cervical spinal mass: a case report - Pelin Analay; Hazal Sevinç; Hilmi Berkan Abacıoğlu; Rahşan Göçmen; Bayram Kaymak; Levent Özçakar (Journal of Yeungnam Medical Science)
Dystonia is a movement disorder characterized by intermittent or sustained muscle contractions that lead to abnormal postures and/or repetitive movements. Although dystonia is traditionally considered a disorder of the basal ganglia, it has been observed in association with lesions at various sites of the motor and sensory pathways, including spinal cord pathologies such as syringomyelia, tumors, and demyelinating lesions. However, there has been an increasing number of focal dystonia cases due to peripheral injuries, such as soft tissue trauma, mononeuropathy, plexopathy, and radiculopathy. In this report, to the best of our knowledge, we present the first case of a patient who developed focal hand dystonia due to cervical mass hemorrhage. We review the literature and discuss possible mechanisms.